2019
DOI: 10.17011/ht/urn.201906123155
|View full text |Cite
|
Sign up to set email alerts
|

Mobile media, gender, and power in rural India

Abstract: This article traces the diffuse connections between mobility and power by exploring how mobile phone use contributed to gendered power relations in rural India. It is based on ethnographic fieldwork on the use of mobile phones, conducted periodically between 2005 and 2013 in the village of Janta in West Bengal, India, and compared to earlier fieldwork in Janta, before the village had any phone system. Analysis of the increased mobility reveals how mobile phone use emerges within interconnected, changing fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In addition, a survey of individuals whose average age is 40,8 has found that men sought help more rarely compared with women, which is associated with their higher status perceived by silence, guaranteeing a more favourable situation (Mulder et al, 2014). Meanwhile, women themselves are more likely to help victims (Mulder et al, 2017), particularly, using technological means of communication in order to create the nets allow to avoid the violation of their rights (Tenhunen, 2019). It has also been found that in response to violence at work, men choose more active, assertiveness-based strategies and are more inclined to analyse their behaviour (Jóhannsdóttir & Ólafsson, 2004), which is explained by gender-related social norms (Notelaers et al, 2019).…”
Section: Violence At Work By Gender and Agementioning
confidence: 99%
“…In addition, a survey of individuals whose average age is 40,8 has found that men sought help more rarely compared with women, which is associated with their higher status perceived by silence, guaranteeing a more favourable situation (Mulder et al, 2014). Meanwhile, women themselves are more likely to help victims (Mulder et al, 2017), particularly, using technological means of communication in order to create the nets allow to avoid the violation of their rights (Tenhunen, 2019). It has also been found that in response to violence at work, men choose more active, assertiveness-based strategies and are more inclined to analyse their behaviour (Jóhannsdóttir & Ólafsson, 2004), which is explained by gender-related social norms (Notelaers et al, 2019).…”
Section: Violence At Work By Gender and Agementioning
confidence: 99%